2014
DOI: 10.17496/kmer.2014.16.2.067
|View full text |Cite
|
Sign up to set email alerts
|

Burnout among Medical School Faculty Members: Incidence and Demographic Characteristics at Three Medical Schools in the Busan and Gyeongnam Area of Korea

Abstract: Few studies have examined burnout among the faculty of medical schools in the Republic of Korea. The aim of this study was to determine the level of burnout and its associated factors among the faculty members of three medical schools in the Busan-Gyeongnam area, and to summarise the available literature on burnout. We conducted the survey using a validated questionnaire that incorporated the Maslach Burnout Inventory-Human Services Survey (MBI-HSS) as well as questions about demographic characteristics, worki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…Burnout was also higher in faculty members with short work experience, and women also experienced more burnout than men [26]. In the study of Seo et al [27], variables such as weekly working hours, health status, work experience and age were identified as factors that increased burnout. However, a study of dental faculty members showed that there was no significant relationship between work experience and working hours per week [28].…”
Section: Factors Associated With the Pa Subscalementioning
confidence: 94%
“…Burnout was also higher in faculty members with short work experience, and women also experienced more burnout than men [26]. In the study of Seo et al [27], variables such as weekly working hours, health status, work experience and age were identified as factors that increased burnout. However, a study of dental faculty members showed that there was no significant relationship between work experience and working hours per week [28].…”
Section: Factors Associated With the Pa Subscalementioning
confidence: 94%
“…20 Compared to 11.8% for emotional exhaustion, 25.3% for depersonalization, and 14.5% for reduced personal accomplishment among professors at three universities in Busan and Gyeongnam area in 2014. 7 This study show a relatively higher degree in all three sub-dimensions of burnout. This increased frequency in burnout in our study may be interpreted partly by the difference of the participants distrubution of the current study, including sampling from all over the country.…”
Section: Discussionmentioning
confidence: 49%
“…Therefore, it needs further investigation to identify what working conditions and school environments affected burnout of medical school faculty members in 2020 compared to that of 2014. 7 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations